Effect of pH during Extraction on the Antioxidant and Antiglycated Activities of Polysaccharides from Opuntia Ficus Indica. Issue 3 (17th November 2015) - Chaouch, Mohamed Aymen; Hafsa, Jawhar; Rihouey, Christophe; Le Cerf, Didier; Majdoub, Hatem
Abstract: The extraction of carbohydrates from O puntia ficus indica cladodes at different pH was carried out by ultrasound followed by ethanol precipitation and dialysis. The extraction yields ranged from 4.6 to 24.5%. The highest content in galacturonic acid was observed for the acidic extract (37.4%). On high‐performance size exclusion chromatography, the average molecular weight of all extracts ranged from 7, 500, 000 to 9, 610, 000 g/mol. The antioxidant activity of extracted polysaccharides was tested by three assays (1, 1‐diphenyl‐2‐picryl‐hydrazil radical scavenging assay, Nitric oxide radical scavenging assay and Linoleic acid peroxidation). The glucose‐induced advanced glycation end‐product (AGE) formation of all extracts was also carried out using in vitro galactose–bovine serum albumin assay. Results showed that the acidic extract exhibited even better antioxidant capacity and inhibitory effect of AGE formation. Practical Applications: Plant extracts containing polysaccharides are widely used in folk medicine for the treatment of skin and epithelium wounds and of mucous membrane irritation. In this case, polysaccharides extracted from O puntia ficus indica cladodes, which is a plant native to South America and cultivated in dry regions as an important nutrient and food source, also are used in traditional medicine for their antiulcer and wound‐healing effects. Thus, O puntia ficus indica cladodes could be a natural candidate for research of herbal complement to the treatment of many diseases. The results found in this study reveal that the extraction under acidic conditions may enhance the antioxidant and antiglycated potential of polysaccharides extracted from O puntia ficus indica cladodes.